REDUPLIKASI MORFEMIS DALAM BAHASA MENTAWAI DI KECAMATAN SIBERUT BARAT KABUPATEN KEPULAUAN MENTAWAI - Hamdi, Fachrul; Juita, Novia (Universitas Negeri Padang, 2019)
This research was conducted to describe (1) the form of morphemic reduplication in Mentawai language, (2) the meaning of reduplication in Mentawai language. This type of research is qualitative research using a descriptive method. The subjects of this study are sentences containing elements of the expression of morphemic reduplication in Mentawai language used by the community in Sigapokna Village, West Siberut District, Mentawai Islands Regency. The data taken is analyzed by the following steps: (1) transcribing the recorded data into written language, (2) identifying the data in accordance with the format provided, (3) classifying the data into morphemic reduplication forms and meanings, ( 4) conclude the data based on the results of the study. There are two findings in this study. First, based on the form, the morphemis reduplication in the Mentawai language used by the community in Sigapokna Village, West Siberut District can be classified into four (1) full reduplication, (2) partial reduplication, (3) affix reduplication, (4) reduplication of phoneme changes. Secondly, based on the meaning of redemption of moemfemis in the Mentawai language used by the people in Sigapokna Village, there were 11 morphemis reduplication meanings, namely (1) many meanings, (2) many meanings explained, (3) unconditional meaning, (4) resembling meanings, ( 5) repeated meanings, (6) meaning of actions carried out without purpose, (7) mutual meaning, (8) meaning of work, (9) meaning rather, (10) meaning of the highest level, (11) meaning intensity of feeling.Keywords: morphemic reduplication, form and meaning.